Analisis Penerimaan Pemustaka pada Layanan Electronic Thesis and Dissertation (ETD) di Perpustakaan Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan Menggunakan Technology Acceptance Model (TAM) - Yani, Fitri; Sayekti, Retno (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
ETD (Electronic Thesis and Dissertation) is one of Padangsidimpuan State Islamic University's Syekh Ali Hasan Ahmad Addary Library's key services for end-user reading. The new service's user satisfaction is unclear.  ETD user acceptability at Padangsidimpuan's Syekh Ali Hasan Ahmad Addary Library needs analysis.  Analysis is needed to test user acceptance of ETD (Electronic Thesis and Dissertation) services at the Syekh Ali Hasan Ahmad Addary Library of Padangsidimpuan.The services taken in this study are ETD (Electronic Thesis and Dissertation) services and are located at the Library of Sheikh Ali Hasan Ahmad Addary State Islamic University Padangsidimpuan using the TAM (Technology Acceptance Model) approach, therefore the author's reason for knowing and analyzing how users receive and use ETD services at the Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University Library. The method used in this study is quantitative research with data collection techniques, namely literature techniques, field research (research files), and distributing questionnaires. Researchers intend to use the TAM method to measure client happiness with ETD offerings. Participants are people who have used ETD services at UIN SYAHADA. The results of TAM X1-Y used to study the opinions of system users or respondents showed that on average 32.825% of respondents answered with Strongly Agree, while 55.7% answered with Agree.  Multiple regression analysis shows that variables related to information system interface design (X1), user attitudes toward information systems (X3), and user behavioral attitudes toward information systems (X4) all have a significant impact on users' actual situation (Y). The simplicity of the user interface (X2) has nothing to do with this. R2 = 0.352, so it seems pretty close. So, external factors account for a total of 35.2% of the variance in users' real-world ISS conditions. The remaining 64.8%, then, were influenced by factors not included in the model.